Answer:
A
Step-by-step explanation:
<h3>Given</h3>
tan(x)²·sin(x) = tan(x)²
<h3>Find</h3>
x on the interval [0, 2π)
<h3>Solution</h3>
Subtract the right side and factor. Then make use of the zero-product rule.
... tan(x)²·sin(x) -tan(x)² = 0
... tan(x)²·(sin(x) -1) = 0
This is an indeterminate form at x = π/2 and undefined at x = 3π/2. We can resolve the indeterminate form by using an identity for tan(x)²:
... tan(x)² = sin(x)²/cos(x)² = sin(x)²/(1 -sin(x)²)
Then our equation becomes
... sin(x)²·(sin(x) -1)/((1 -sin(x))(1 +sin(x))) = 0
... -sin(x)²/(1 +sin(x)) = 0
Now, we know the only solutions are found where sin(x) = 0, at ...
... x ∈ {0, π}
Answer:
19,14
Step-by-step explanation:
x=5+y
x+ y= 33
we will solve using substitution
(5+y) +y= 33
5+y+y=33
5+2y=33
subtract 5 from both sides
2y=28
y=14
We got y now we will find what x is
for this, we will substitute y's value (14) into the first equation
x=5+(14)
x=19
we got x too
Answer:
x = 6
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define Equation</u>
3 - 2x = -1.5x
<u>Step 2: Solve for </u><em><u>x</u></em>
- Add 2x on both sides: 3 = 0.5x
- Divide 0.5 on both sides: 6 = x
- Rewrite: x = 6
<u>Step 3: Check</u>
<em>Plug in x into the original equation to verify it's a solution.</em>
- Substitute in<em> x</em>: 3 - 2(6) = -1.5(6)
- Multiply: 3 - 12 = -9
- Subtract: -9 = -9
Here we see that -9 does indeed equal -9.
∴ x = 6 is the solution to the equation.